Stanze per fare l’amore. Illusione e seduzione in quattro interni del Novecento - Saitto, Viviana (Firenze Architettura, 2019)
Four well-known 20th century interiors demonstrate that seduction is the space for play, illusion and challenge. Ettore Sottsass’ camera per fare l’amore and the spaces devised for repose at Carlo Mollino’s Casa Devalle in Turin, Carlo Scarpa’s Casa Ottolonghi in Bardolino and Le Corbusier’s Villa Savoye in Poissy, were designed to se-ducere, to lead aside, they are the mirror of the unconscious and of desire.